Back-analysis of in-pit dump slope failure and remediation results at Bara Anugrah Sejahtera open pit coal mine, Indonesia - Rachmad, L.; Aryanda, D.; Daroji, M. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Bara Anugrah Sejahtera (BAS) Mine experienced a massive slope movement during the building of its overburden in-pit dump. The total material affected by this movement was around 47,000 m3 and covering an area of 10,000 m2. This movement created not only in-pit dump failure but also floor heaving along the highwall. The failure stopped the mining operation for about 12 months, and during that period, geology and geotechnical investigation was carried on. In Indonesia, the practice of overburden in an in-pit dump is typical due to the limitation of ‘free and already compensated’ land inside the mining permit boundary for placing the out-pit dump. Another reason is the requirements for getting forestry permits for other nominated out-pit dump areas. Conventionally, an in-pit dump is carried out in one part of the pit walls (sidewall or highwall) that has reached its final geometry state. The finalised pit wall is used as a buttress so that the condition of stability can be maintained. For the BAS case, the final position of the pit is still going to happen in a few years, while the area for the out-pit dump is limited. Therefore, the BAS mine in-pit dump has to be placed without buttressing to any finalised pit wall. From detailed investigation, the existence of the montmorillonite clay layer below the pit floor and a geological structure along the strike of the pit were suspected to be the leading causes of the movement and heaving. Back analyses were carried out to validate material properties by comparing actual and modelling conditions. Models were also used to determine the most appropriate remediation strategy from geotechnical, operational, and financial perspectives. BAS has implemented the selected remediation strategy with success. This paper discusses the back-analysis to estimate montmorillonite and structure properties. Also, it explains the evaluation of several remediation options using those properties, the implementation of the selected option, and its current results.